(untitled) (Fiep Bulletin - online, 2014)
The goal of the present work was to study the oxidative stress and lipid profile in malnourished animals submitted to physical exercise (swimming 30 minutes/day, 5 days/week during 8 weeks). Twenty eight female Fisher rats were divided into four groups: Sedentary Control (SC), Trained Control (TC), Sedentary Malnourished (SM) and Trained Malnourished (TM). We have concluded that: a) the applied swimming physical training did not cause muscle damage detectable by the biochemical marker creatine kinase, although it caused positive modifications in the body weight of the TM animals; b) malnutrition promoted a significant increase in the concentrations of total and HDL cholesterol but physical exercise was not capable of reverting this situation; c) The rise of HDL concentration in malnourished animals were not followed by increase in the paraoxonase activity and this allows us to formulate the hypothesis that HDL of these animals might not act as antioxidants as expected for these molecules; d) the increase in total, free and bound sulphydrils in malnourished animals needs to be studied together with other markers of oxidative stress.